Proceedings of the Twenty-Eighth International Joint Conference on Artificial Intelligence 2019
DOI: 10.24963/ijcai.2019/99
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Bi-directional Attention Network for Human Motion Recovery

Abstract: Human motion capture (mocap) data, recording the movement of markers attached to specific joints, has gradually become the most popular solution of animation production. However, the raw motion data are often corrupted due to joint occlusion, marker shedding and the lack of equipment precision, which severely limits the performance in real-world applications. Since human motion is essentially a sequential data, the latest methods resort to variants of long short-time memory network (LSTM) to solve related prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…They are designed for specific problems and usually cannot solve other tasks without retraining mapping functions even if the problems are similar. For example, training a network for random joint missing samples is not easily re-applied to continuous joint corruption scenarios or to solve motion gaps [10]. Deep learning-based approaches typically generate the trained model from the training database.…”
Section: Preliminaries 21 Signal Inverse Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…They are designed for specific problems and usually cannot solve other tasks without retraining mapping functions even if the problems are similar. For example, training a network for random joint missing samples is not easily re-applied to continuous joint corruption scenarios or to solve motion gaps [10]. Deep learning-based approaches typically generate the trained model from the training database.…”
Section: Preliminaries 21 Signal Inverse Problemmentioning
confidence: 99%
“…Nowadays, Deep Neural Networks (DNNs) have been widely exploited in various tasks related to human motion [3,7,26]. They are committed to training an optimal model from vast mount training samples, and then use this trained model to repair damaged sequences in testing time [10]. Despite remarkable achievements, however, training data can hardly cover all action types due to the non-enumerability of human motion.…”
Section: Introductionmentioning
confidence: 99%
“…Mall et al [11] trained a set of filters using a deep, bidirectional, recurrent framework for clean, noisy and incomplete mocap data. In 2019, Cui et al [44] proposed a bidirectional attention network for missing data recovery, and their embedded attention mechanism can decide where to borrow information from and use this information to recover corrupted frames. The above deep-learning-based methods are action agnostic but noise specific, i.e., these methods can be trained by largescale data with a specified type of noise (such as Gaussian noise or missing data) and a heterogeneous mix of action types, and the network can refine any action with that noise type.…”
Section: Refinement Neural Networkmentioning
confidence: 99%
“…Tang et al 17 introduced a RNN‐based motion prediction system by analyzing the observed motion sequences. Cui et al 7 proposed a bidirectional RNN with an attention mechanism to accurately infer the missing joints. In contrast to ours, unsupervised motion retargeting systems have been proposed in References 18,19.…”
Section: Related Workmentioning
confidence: 99%
“…Against this backdrop, based on deep learning frameworks that can efficiently handle large amounts of motion data, 5‐7 here, we propose a novel deep autoencoder that combines the deep convolutional inverse graphics network (DC‐IGN) 8 and U‐Net 9 shown in Figure 1 to efficiently retarget human motion. Our approach handles various types of motions to be retargeted and is sufficiently fast to be used as a real‐time application.…”
Section: Introductionmentioning
confidence: 99%